O impacto sociocultural na identidade Taurepang na Comunidade Sorocaima I - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The present research examined the socio-cultural impacton the identity of the people in the indigenous community Taurepang Sorocaima I, where live approximately 43 families, totaling 207 individuals. The community is located on the margins of BR 174, far northern Brazil near the Brazil border and the Bolivarian Republic of Venezuela, with land access. It was noted the socio-cultural impact in the form of constant changes of daily life in that, although these transformations take place, the identity remains alive and present in the present day, represented by the symbols and signs in life of this people. The study and nature of this research was qualitative with the methodological procedures of semi-structured interviews, using participant observation. As instrumental, used the questionnaire. The result of this investigation came the Church and the school as two major factors that impacted directly on everyday life of the people, which was concerned with maintaining the rules and norms of Adventist doctrine in society Taurepang, in the name of God. There was the extent to which the identity of the people Taurepang continues to render on sociocultural impacts of processes, in particular by means of religion and education.
Keywords: Comunidade Indígena Sorocaima I - Brasil; Cultura e Religião; Culture and Religion; OUTROS